Plant Protein Innovation: Optimizing Tri-Source Vegan Protein Isolates with Optimized Nutrition and Functionality - Hend A. Hamed (23752974) (2025)
This conference contribution was presented by Hend A. Hamed, Mennatallah M. A. El-Geddawy, Mahmoud A. Basry, Walaa Kobacy. Sohag University, Assuit University, Agricultural Genetic Engineering Research Institute. Egypt. (18th Edition of the Qatar University Life Sciences Symposium Bio-Environment: Advances and Innovations. 2025). The rising global demand for sustainable, plant-based protein sources has intensified the exploration of legumes such as faba bean, lupine, and soybean. This study builds upon previously published findings to provide a comprehensive assessment of protein isolates derived from faba bean (FPI), lupine (LPI), soybean (SPI), and their equal-proportion mixture (MPI). Using the AE-IP extraction technique, all isolates demonstrated high protein content, with SPI exhibiting the highest concentration (96.15%). However, MPI stood out with a well-balanced nutritional profile, enhanced digestibility (95.35%), and reduced antinutritional factors such as tannins and phytic acid. From a functional standpoint, MPI displayed superior emulsifying activity (EAI), water- and oil-binding capacities (WBC and OBC), and structural stability under high shear stress—traits essential for various food applications. Notably, MPI also presented the most stable thermal denaturation behavior (DSC) and a favorable particle charge (-37.1 mV), suggesting enhanced colloidal stability. Scanning electron microscopy revealed that MPI exhibits a hybrid microstructure with angular edges, smooth surfaces, and fine particulate distribution, reflecting contributions from all three individual isolates PCR analysis confirmed the non-GMO status of all protein isolates. Collectively, these findings highlight MPI as a promising, nutrient-dense, and functionally robust plant-based protein isolate. Its chemical integrity, excellent digestibility, and versatile techno-functional properties position it as a compelling alternative to traditional protein sources in both dietary supplements and industrial food formulations. Other Information Conference information: 18th Edition of the Qatar University Life Sciences Symposium Bio-Environment: Advances and Innovations. (26 - 27 Nov 2025, Qatar University, Doha - Qatar) License: https://creativecommons.org/licenses/by/4.0/ See the conference information on the organizer's website: https://www.qu.edu.qa/en-us/conference/QULSS2025/Pages/default.aspx